Impaired calcium homeostasis via advanced glycation end products promotes apoptosis through endoplasmic reticulum stress in human nucleus pulposus cells and exacerbates intervertebral disc degeneration in rats. (9th July 2019) - Luo, Rongjin; Song, Yu; Liao, Zhiwei; Yin, Huipeng; Zhan, Shengfeng; Wang, Kun; Li, Shuai; Li, Gaocai; Ma, Liang; Lu, Saideng; Zhang, Yukun; Yang, Cao
Abstract : Previous studies identified advanced glycation end products (AGEs) accumulation in the intervertebral disc (IVD) as an essential risk factor associated with IVD degeneration via accelerated cell apoptosis and impeded extracellular‐matrix metabolism; however, the underlying mechanisms have not been fully elucidated. Here, we investigated the effects and mechanisms of AGEs‐mediated apoptosis in vitro and in vivo . We evaluated the effects of AGEs on endoplasmic reticulum (ER) stress, apoptosis, and subcellular calcium (Ca 2+ ) redistribution. Our data indicated time‐ and concentration‐dependent upregulation of ER‐stress responses in AGEs‐treated nucleus pulposus (NP) cells. Additionally, we observed marked suppression of AGEs‐mediated apoptosis following the inhibition of ER stress using 4‐phenylbutyric acid. Moreover, AGEs‐induced sustained cytosolic Ca 2+ ([Ca 2+ ]c) elevation and ER luminal Ca 2+ ([Ca 2+ ]er) depletion in a concentration‐ and time‐dependent manner in NP cells. Furthermore, we observed significant increases and decreases in levels of the ER‐resident Ca 2+ ‐release channels inositol 1, 4, 5‐triphosphate receptor and ryanodine receptor and ER Ca 2+ ‐reuptake pumps sarco/endoplasmic reticulum Ca 2+ ‐ATPase, respectively. Pharmacologically blocking ER Ca 2+ release using Ca 2+ antagonists significantly ameliorated Ca 2+ dyshomeostasis, ER stress, and subsequent apoptosis in NP cells and partially attenuated the progression of IVD degeneration in vivo . These results demonstrated that impaired Ca 2+ homeostasis plays an essential role in AGEs‐mediated ER stress and subsequent apoptosis in NP cells, with blockage of ER Ca 2+ release partially ameliorating subcellular Ca 2+ redistribution, ER stress, and apoptosis. Our findings provide novel mechanistic insight into the role of AGEs in the pathogenesis of IVD degeneration and a potential therapeutic strategy. Abstract : The accumulation of advanced glycation end products (AGEs) in the intervertebral disc (IVD) has been identified as a key risk factor associated with IVD degeneration. Here, we show that disruption of intracellular calcium homeostasis plays a pivotal role in AGEs‐induced activation of endoplasmic reticulum (ER) stress and apoptosis, molecular events underlying degeneration. Pharmacological inhibition of calcium release from ER calcium channels significantly ameliorated AEGs‐induced disturbance of calcium homeostasis, ER stress, and downstream apoptosis in degenerated nucleus pulposus cells and in vivo .